Respuesta :
Answer:
[tex]x^{2}-4x+10[/tex]
Step-by-step explanation:
[tex](x-4x^{2}+7)-(-5x^{2}+5x-3)\\x-4x^{2}+7+5x^{2}-5x+3\\x^{2}-4x+10[/tex]
●✴︎✴︎✴︎✴︎✴︎✴︎✴︎✴︎❀✴︎✴︎✴︎✴︎✴︎✴︎✴︎✴︎✴︎●
Hi my lil bunny!
❧⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯☙
Let's simplify step-by-step.
[tex]( x - 4x^2 + 7 ) - ( -5x^2 + 5x - 3)[/tex]
Distribute the Negative Sign:
[tex]= x - 4^2 + 7 + -1 ( -5x^2 + 5x -3) \\= x + -4x^2 + 7 + -1 ( -5x^2) + -1 (5x) + ( -1) (-3)\\= x + -4x^2 + 7+ 5x^2 + -5x + 3[/tex]
Combine Like Terms:
[tex]= x + -4x^2 + 7 + 5x^2 + -5x + 3 \\= (-4x^2 + 5x^2) + ( x + -5x) + ( 7 + 3) \\= x^2 + -4x + 10[/tex]
Answer : [tex]\boxed {x^2 -4x + 10}[/tex]
❧⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯☙
●✴︎✴︎✴︎✴︎✴︎✴︎✴︎✴︎❀✴︎✴︎✴︎✴︎✴︎✴︎✴︎✴︎✴︎●
Have a great day/night!
❀*May*❀